RIGHT AND UNLAWFUL IN DETERMINATION OF SOCIAL RELATIONS - Орденов, С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
In the article, in the context of the main discursive and legal characteristics of societies of different types, reveal the structural components that determine the right and wrong in the system of social relations. It has been established that these determinants determine the respective roles and functions of law, and are responsible for the practical realization of rights and freedoms in societies of an individualistic and traditionalist type. In individualist societies, the legal function is permissive-regulating, and is to regulate existing social relations based on the principles of law that make up its essence. In traditionalist societies, the regulator of relations is not legal norms, but unwritten rules of their social action. The very norms of positive law serve as means of regulated and regulated access to the benefits of representatives of various stratified groups. Therefore, the function of law there is prohibitive-distributive, and is to reduce social mobility. This leads to the repressive role of law, which unfolds in the non-liberal system of relations as its opposite, that is, in essence, is wrong.